Estudo dos fosfatos do distrito pegmatítico de Conselheiro Pena, Minas Gerais - Ricardo Augusto Scholz Cipriano (2006)
The mining in pegmatites of the Conselheiro Pena Pegmatitic District is responsible for theproduction of an important amount of production of gemstones and collectors minerals. The rarephosphate minerals are commonplace in the pegmatite bodies in this District. Minerals such asbrazilianite, scorzalite and souzalite were discovered in the Córrego Frio Pegmatite, Divino dasLaranjeiras region, and the moraesite, barbosalite, faheite, frondelite, lipscombite and tavorite werediscovered in the Sapucaia Pegmatite, Galiléia region.The pegmatites are mined for industrial minerals and gemstones. The most importantsgemological minerals are the tourmaline, beryl, quartz, kunzite, hiddenite and in less quantityphosphatic minerals such as brazilianite, amblygonite/montebrasite, apatite and eosphorite.The phosphatic mineralogy found in the pegmatite bodies don´t show any relation betweenthe enrichment in phosphate minerals and degree of diferenciation of pegmatites. Twentypegmatites were sampled and divided in 5 types, using the primary phosphatic mineralogy, or theabsence of phosphatic primary phases.Several phosphatic paragenesis were found, and some of this are composed by primaryphosphates and their alteration products. Some secondaries phosphates occur such as hydrotermalor supergenic alteration.The systematic study of childrenite-eosphorite and ernstite show the presence of Fe(III) in theoctahedric site of Al(III).